Single-Molecule Kinetics Reveal Cation-Promoted DNA Duplex Formation Through Ordering of Single-Stranded Helices - Dupuis, Nicholas F. (The Biophysical Society, 2013)
In this work, the kinetics of short, fully complementary oligonucleotides are investigated at the single-molecule level. Constructs 6–9 bp in length exhibit single exponential kinetics over 2 orders of magnitude time for both forward (k(on), association) and reverse (k(off), dissociation) processes. Bimolecular rate constants for association are weakly sensitive to the number of basepairs in the duplex, with a 2.5-fold increase between 9 bp (k′(on) = 2.1(1) × 10(6) M(−1) s(−1)) and 6 bp (k′(on) = 5.0(1) × 10(6) M(−1) s(−1)) sequences. In sharp contrast, however, dissociation rate constants prove to be exponentially sensitive to sequence length, varying by nearly 600-fold over the same 9 bp (k(off) = 0.024 s(−1)) to 6 bp (k(off) = 14 s(−1)) range. The 8 bp sequence is explored in more detail, and the NaCl dependence of k(on) and k(off) is measured. Interestingly, k(on)increases by >40-fold (k(on) = 0.10(1) s(−1) to 4.0(4) s(−1) between [NaCl] = 25 mM and 1 M), whereas in contrast, k(off)decreases by fourfold (0.72(3) s(−1) to 0.17(7) s(−1)) over the same range of conditions. Thus, the equilibrium constant (K(eq)) increases by ≈160, largely due to changes in the association rate, k(on). Finally, temperature-dependent measurements reveal that increased [NaCl] reduces the overall exothermicity (ΔΔH° > 0) of duplex formation, albeit by an amount smaller than the reduction in entropic penalty (−TΔΔS° < 0). This reduced entropic cost is attributed to a cation-facilitated preordering of the two single-stranded species, which lowers the association free-energy barrier and in turn accelerates the rate of duplex formation.